PENGARUH ENDORSEMENT PUBLIC FIGURE TERHADAP MINAT BELI KONSUMEN PADA PRODUK SKINCARE - Sevia Diah Oktaviana; Mawar Sri Puji Efendi; Nur Aini (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
Endorsement is one way of promotion by using an advertising strategy and utilizing public figures to support in promoting products. The promotion can be done through social media such as Instagram, YouTube, TikTok, etc. because it has a wide reach. Generally, endorsement is done through cooperation with public figures, one of which is celebrities because they have many followers. A public figure (celebrity) can be defined as someone who is widely highlighted by the media and has a major influence on social behavior and trends, generally celebrities have roles related to the world of entertainment (influencers), sports, or other entertainment fields that invite public attention. One of the research objectives is to find out in depth about whether or not public figure endorsements have an influence on consumer buying interest in skincare products. The method used is quantitative with a descriptive approach and uses primary data collection techniques obtained through distributing questionnaires online with a sample of 100 respondents via Google-Form. Then secondary data in the form of literature reviews from relevant articles. The results in the study indicate that the results of the research test show that public figure endorsements influence consumer buying interest in skincare products.